Disruption of IL-33 Signaling Limits Early CD8+ T Cell Effector Function Leading to Exhaustion in Murine Hemophagocytic Lymphohistiocytosis - Rood, Julia E.; Burn, Thomas N.; Neal, Vanessa; Chu, Niansheng; Behrens, Edward M. (Frontiers in Immunology, 2018)
Danger signals mediated through ST2, the interleukin-33 (IL-33) receptor, amplify CD8+ T cell-mediated inflammation in the murine model of familial hemophagocytic lymphohistiocytosis type 2 (FHL2), and blockade of ST2 provides a potential therapeutic strategy in this disease. However, the long-term effects of disrupting IL-33/ST2 signaling on the CD8+ T cell compartment are unknown. Here, we examined the evolution of the T cell response in murine FHL type 2 in the absence of ST2 signaling and found that CD8+ T cells gradually undergo exhaustion, similar to a related nonfatal FHL model. ST2 inhibition indirectly promotes CD8+ T cell exhaustion, and in contrast to other forms of FHL, reversal of exhaustion does not affect mortality. Disruption of IL-33 signaling exerts a more significant impact on the CD8+ T cell compartment early in the course of disease by intrinsically limiting CD8+ T cell proliferative and cytokine production capacity. Our data thus suggest that while ST2 blockade ultimately enables the development of CD8+ T cell exhaustion in late-stage murine FHL2, exhaustion is merely an effect, rather than the cause, of extended survival in these mice. The acute impact of ST2 inhibition on both the quantity and quality of the effector CD8+ T cell response more likely underlies the protective benefits of this treatment. This study provides evidence that redefines the relationship between CD8+ T cell exhaustion and mortality in murine FHL and supports the therapeutic use of ST2 blockade during the acute stage of disease.